Migration, urbanization, industrialization, export promotion and economic development - Chowdhury, Mehdi Mahmud (BRAC University, 2010)
Import substitution was the main trend of industrial and trade policy after the World War Two. This policy in now disfavored and almost all developing countries are at present trying to increase exports to become developed. In this paper we discussed about this issue and linked it with the migration and urbanization problem of the developing world. Economic theory once viewed migration as a tool for economic development as it enables industrial sector to get additional labor. This view has changed but we argued that export promotion will encourage migration and urbanization as export sectors of developing countries are usually manufacture and urban based sectors. We discussed about the policy issues relevant in this situation.